Dealing with the Media - Jarvis Miller (Journal of Applied Communications, 1979)
As a research administrator, I believe totally in the validity of our research mission and goals. These goals are consistent with and in the best interest of our tax-paying citizens. (Papers from the National Agricultural Science Information Conference, Ames, Iowa.)